Modern economic growth: rate, structure, and spread - Kuznets, Simon Smith (New Haven, Yale University Press, 1966)
This book examines problem associated with economic growth of nations across the world, putting into cognizance the variant among the population size, revenue generation and economic unbalance.
Bibliography: p. 511-520.
asm; 18/02/20
Loans
Keywords: Economic development